Steady as she blows [wind power, energy storage]. - Fairley, P.
Power electronics and exotic energy storage devices are making wind power steady enough to compete with conventional electricity sources. Systems based on advanced power electronics and energy storage devices are massaging and managing power flows from wind turbines, enabling them to contribute to electricity grids without putting those grids at risk. Not only are the technologies making wind power more palatable to grid operators, they are even making it possible for engineers to finally harness wind energy's tremendous potential in wind-swept, remote locales. This article discusses the power electronic and energy storage technologies used in wind power.
Keywords: Electricity grids; Energy storage; Power flows control; Wind power; Wind turbines; Wind-swept remote locales